2011
DOI: 10.1186/1471-2334-11-235
|View full text |Cite
|
Sign up to set email alerts
|

Canadian oncogenic human papillomavirus cervical infection prevalence: Systematic review and meta-analysis

Abstract: BackgroundOncogenic human papillomavirus (HPV) infection prevalence is required to determine optimal vaccination strategies. We systematically reviewed the prevalence of oncogenic cervical HPV infection among Canadian females prior to immunization.MethodsWe included studies reporting DNA-confirmed oncogenic HPV prevalence estimates among Canadian females identified through searching electronic databases (e.g., MEDLINE) and public health websites. Two independent reviewers screened literature results, abstracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 67 publications
2
19
0
3
Order By: Relevance
“…Our study population consisted of women with various genital complaints and nearly half of the study participants (45.2%) presented HPV positivity which was significantly higher compared to studies from Turkey [16,17] and several western countries [18,19] and similar to some developing countries including Latin America and the Caribbean [20,21]. Apart from these elevated rates of HPV infection, we also found that HPV 16 and HPV 58 was associated with common abnormal cervical smear test results including high rates of ASCUS, LSIL and HSIL.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our study population consisted of women with various genital complaints and nearly half of the study participants (45.2%) presented HPV positivity which was significantly higher compared to studies from Turkey [16,17] and several western countries [18,19] and similar to some developing countries including Latin America and the Caribbean [20,21]. Apart from these elevated rates of HPV infection, we also found that HPV 16 and HPV 58 was associated with common abnormal cervical smear test results including high rates of ASCUS, LSIL and HSIL.…”
Section: Discussionmentioning
confidence: 94%
“…Briefly HPV genotyping performed by the F-HPV typing™ multiplex PCR (Molgentix SL, Barcelona, Spain). The assay uses 16 specific primers amplifying within E6 and E7 regions of the HPV genome and permits the detection of 13 high risk genotypes (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) and two low-risk genotypes (6 and 11). The presence of DNA of these HPV subtypes were detected by multiplex PCR amplification using type specific primers [14,15].…”
Section: Dna Isolation and Hpv Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…As mulheres positivas para o HIV apresentaram, neste estudo, 6,3% de infecções por múltiplos tipos de HPV, porcentagem menor do que os 64,8% encontrados em outros estudos 20,34 . De acordo com metanálise avaliando a prevalência da infecção cervical pelo HPV em várias regiões do mundo, a prevalência do HPV está fortemente relacionada à idade, tendo em vista que a infecção cervical pelo HPV é mais intensa nas mulheres jovens, com pico de prevalência igual ou inferior a 25 anos, diminuindo nas mulheres com mais idade 2 . De acordo com outro estudo, um segundo pico de prevalência foi observado em algumas regiões, em mulheres entre 35 e 50 anos, provavelmente referente a novas infecções relacionadas a mudanças no comportamento sexual dessas mulheres 8 .…”
Section: Métodosunclassified
“…A infecção pelo HPV é considerada a doença sexualmente transmissível (DST) mais prevalente no mundo. A relação entre o câncer de colo e a infecção pelo HPV está bem estabelecida na literatura, com detecção de HPV de alto risco em quase 100% dos casos 2 . Estudo de metanálise encontrou o HPV em 87% dos casos de câncer de toda a população mundial 3 .…”
Section: Introductionunclassified